Effects of High Temperature Frying of Spinach Leaves in Sunflower Oil on Carotenoids, Chlorophylls, and Tocopherol Composition - Zeb, Alam; Nisar, Parveen (Frontiers in Chemistry, 2017)
Spinach is one of the highly consumed vegetable, with significant nutritional and beneficial properties. This study revealed for the first time, the effects of high temperature frying on the carotenoids, chlorophylls and tocopherol contents of spinach leaves. Spinach leaves were thermally processed in the sunflower oil for 15, 30, 45 and 60 min at 250 °C. HPLC-DAD results revealed a total of eight carotenoids, four chlorophylls and α-tocopherol in the spinach leaves. Lutein, neoxanthin, violaxanthin and β-carotene-5,6-epoxide were the major carotenoids, while chlorophyll a and b' were present in higher amounts. Frying of spinach leaves increased significantly the amount of α-tocopherol, β-carotene-5,6-epoxide, luteoxanthin, lutein and its Z-isomers and chlorophyll b' isomer. There was a dose dependent decrease in the amounts of neoxanthin, violaxanthin, chlorophyll b, b' and chlorophyll a with increase of frying time. The increase of frying time increased the total phenolic contents in spinach leaves and fried sunflower oil samples. Chemical characteristics such as peroxide values, free fatty acids, conjugated dienes, conjugated trienes and radical scavenging activity were significantly affected by frying, while spinach leaves increased the stability of the frying oil. This study can be used to improve the quality of fried vegetable leaves or their products at high temperature frying in food industries for increasing consumer acceptability.